How was remote technology accepted among cardiac rehabilitees in outpatient self-rehabilitation context? - Säteri, Sanna; Heinonen, Ari; Sjögren, Tuulikki (European Journal of Physiotherapy, 2024)
The purpose of this study was to investigate cardiac rehabilitees' experiences with wrist-worn activity monitor (Fitbit Charge HR) and internet-based coaching software (Movendos m-coach) in outpatient rehabilitation to promote physical activity and a healthy lifestyle. A 12-month cardiac rehabilitation intervention consisted of three 5-day inpatient periods in a rehabilitation centre, between which participants (n = 32; age mean 62.3 years old (SD 6.3), men n = 24 (75%)) used an activity monitor and internet-based coaching software at home. Experiences with the use of technologies were measured at the end of the 12-month intervention with a questionnaire that was designed using the framework of the Technology Acceptance Model (Likert scale 1–7; 1 = strongly agree and 7 = strongly disagree). Data analysis was based on indicators describing the average experiences and Spearman's correlation coefficient. Both technologies had positive acceptance (internet application mean: 3.2, 95% CI: 2.6–3.7; activity monitor mean 2.1, 95% CI: 1.7–2.5). Sociodemographic factors, physical activity, and familiarity with using technology in daily life were not correlated with technology acceptance of either technology. Cardiac rehabilitees had positive acceptance on wrist worn activity monitor and internet-based coaching software, which suggests the use of these tools in outpatient cardiac rehabilitation. ISRCTN Registry, url: , reg. number: ISRCTN61225589